2022
DOI: 10.1155/2022/9978235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Sargassum angustifolium Extract on Methamphetamine-Induced Cytotoxicity in SH-SY5Y Cells

Abstract: This study aimed to assess the effect of the Sargassum angustifolium extract in methamphetamine-induced SH-SY5Y cells death. The brown algae S. angustifolium was extracted with 80% ethanol. The SH-SY5Y cells were treated with different concentrations of methamphetamine to measure IC50 .. The MTT test was used to assess the toxic effect of the S. angustifolium extract in SH-SY5Y cells. SH-SY5Y cells’ survival was measured whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The upregulation of proapoptotic proteins is consistent with the findings that Meth treatment caused the release of mitochondrial Cyt c protein and apoptosis-inducing factors into the cytosol 32 , 33 . A recent study by Salari et al reported an increased release of Cyt c from mitochondria and an increased Bax to Bcl-2 ratio in the presence of Meth 34 . The factors released from mitochondria have been shown to participate in Meth-induced apoptosis by activating Cas9 and 3 and breaking down several structural cellular proteins 35 .…”
Section: Discussionmentioning
confidence: 92%
“…The upregulation of proapoptotic proteins is consistent with the findings that Meth treatment caused the release of mitochondrial Cyt c protein and apoptosis-inducing factors into the cytosol 32 , 33 . A recent study by Salari et al reported an increased release of Cyt c from mitochondria and an increased Bax to Bcl-2 ratio in the presence of Meth 34 . The factors released from mitochondria have been shown to participate in Meth-induced apoptosis by activating Cas9 and 3 and breaking down several structural cellular proteins 35 .…”
Section: Discussionmentioning
confidence: 92%
“…extract showed low cytotoxicity against Hep-2 and MCF-7 cancer cells with IC 50 values above 100 µg/mL. [ 25 ] Another report also indicated that Sargassum anguistifolium extract showed no cytotoxicity in SH-SY5Y cells and prevented methamphetamine toxic effects in SH-SY5Y cells [ 26 ]. However, some reports indicate that brown macroalgae Sargassum could be a valuable source of potential anticancer compounds, such as fucoidan.…”
Section: Resultsmentioning
confidence: 99%
“…The synthetic drug methamphetamine (MA) has a neurodegenerative effect on the human brain and can increase the generation of ROS through dopamine oxidation. In fact, a hydroethanolic extract of S. angustifolium rich in polyphenols, including gallic acid, protocatechuic acid, gentisic acid, and hydroxybenzoic acid, led to a decrease in ROS generation on MA-exposed SH-SY5Y dopaminergic cells with doses of 80 and 160 μg/mL [ 127 ]. Similarly, fucoxanthin isolated from S. horneri prevented the effects of MA on ROS, significantly reducing their production ( p < 0.05) and causing a significant increase in HO-1 expression in PC12 cells at 3 µM [ 128 ].…”
Section: Bioactive Potential Of Sargassum Antioxidant Secondary Metab...mentioning
confidence: 99%